PERENCANAAN PEMANFAATAN SISTEM PEMANENAN AIR HUJAN (PAH) DALAM MENDUKUNG PENERAPAN ECODRAIN DI KAMPUS B UNIVERSITAS NEGERI JAKARTA - Fauziah Ismahyanti; Rosmawita Saleh; Arris Maulana (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
This research is done to plan rainwater harvesting so that it can be used as an alternative water source on the campus B UNJ so it is expected to reduce groundwater use that can cause a puddle. The method used in the PAH development plan is a water balance method. This method compares the level of demand with water volume that can be accommodated or the availability of water (supply). Based on the results of the analysis, it was found that the potential for rainwater in the FIO office building A was 1773.95 m3 , FMIPA building B was 1904.62 m3 , the FIO lecture building C was 1613.21 m3 and the Ulul Albab mosque was 512.16 m3 . Potential rainwater obtained cistern PAH capacity of 200 m3 by saving water needs by 30% in building A FIO, building B FMIPA, and building C FIO. The capacity of the PAH cistern is 80 m3 by saving the water needs of the Ulul Albab mosque by 13.3%. Placement of the PAH cistern under the ground with a ground water system. Ecodrainage application by utilizing the PAH system can reduce drainage load by 0.158 m3 /second or 13.9% from rainwater runoff.